Determination of bioclimatic comfort in Sirjan desert - Tayebeh Mahmoodi; Mohammad Reza Iravani (Management Science Letters, 2012)
Climate plays an important role in assessment of quality of outdoor built environments and bioclimatic comfort physiologically influences on human body's characteristics. In this paper, we present an empirical study on bioclimatic comfort in Sirjan desert located in the province of Kerman, Iran. The results of our study shows that velocity of air can reach one meter per second during the daily hours only during the month of September, which causes comfort on people's body. However, even this velocity cannot cause comfort during the night. During the months of March, April and October, whether maintains a velocity of 0.1 meter/second, which brings comfort and it is possible to live with simple dress. During the months of May, June and July it is possible to reach comfort with simple cover during the night. It is possible to reach the same condition with thicker coverage in nightly hours during the months of May and September. However, it is not possible to reach comfort with thick dress any nightly hours of year.